IMPLEMENTATION OF LAW NUMBER 35 OF 2014 CONCERNING PROTECTION OF CHILD AGAINST CHILD VIOLENCE IN THE SCHOOL ENVIRONMENT - Dastina Dastina (Sean Institute, 2021)
The formulation of the problem in this study are 1) What is the role of the law on child protection against child abuse in the school environment? 2) Factors that support and hinder the implementation of child protection in the school environment? In answering these problems, the author uses field research or field research with the approach used is an empirical juridical approach. Data collection methods used were observation, questionnaires and interviews. The results of this study indicate the role of the law on child protection in the school environment. In accordance with article 54 of Law Number 35 of 2014 it has been implemented but violence in schools still occurs both psychologically and physically, both between students and from education staff. The violence that most often occurs in the school environment is psychological violence between students. The factors that support the implementation of child protection in the school environment are by implementing non-violent schools, religious education lessons that teach gentle behavior, prevention by instilling character in both students and education staff. the school environment, namely 1) Lack of knowledge from teachers or education staff that physical and psychological violence is not always effective either because of psychological problems that cause obstacles in managing emotions so that teachers or education staff become more sensitive and reactive, the existence of work pressure or because of the authoritarian pattern which is still commonly used in teaching patterns in Indonesia 2) Students who have traits that tend to be weak usually make stronger students to do violence against weak students so that they feel great. Both of these attitudes can be influenced by family parenting and from the child's environment. The implications of this study are 1) Schools should implement non-violent education, by not only emphasizing cognitive abilities but also paying attention to children's affective abilities and psychomotor abilities so that children are not only knowledgeable but also schools pay attention to children's skills. psychic.